ARTIFICIAL INTELLIGENCE (AI) IN LANGUAGE LEARNING (ENGLISH AND ARABIC CLASS): STUDENTS’ AND TEACHERS’ EXPERIENCE AND PERCEPTIONS - Yatri, Deni; Anugerahwati, Mirjam; Setyowati, Lestari (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2023)
This study explores the integration of Artificial Intelligence (AI) in language learning within English and Arabic classes. The research involved 18 participants, encompassing learners and teachers of both languages. It aims to understand their experiences, perceptions, and challenges when incorporating AI into language education. Learners demonstrated diverse use of AI tools such as Chat GPT, Grammarly, and Elsa, leveraging them for various language learning aspects including writing enhancement, speaking practice, and translation. While English learners extensively employed multiple AI tools, Arabic learners primarily relied on Chat GPT for scientific paper writing, with limited exploration of other available AI variations. Participants generally viewed AI integration positively, recognizing its facilitative role in learning, yet raised concerns about potential over-reliance, plagiarism risks, reduced creativity, and inaccuracies. Teachers relied on Grammarly for grammar correction and Chat GPT for language tasks, emphasizing the need for human validation to ensure contextual accuracy despite acknowledging AI benefits. Challenges identified included limited access due to premium features, connectivity issues, and ethical concerns surrounding AI-generated content. The study emphasizes AI's significance as a valuable aid in language education while cautioning against excessive reliance. It highlights the necessity for human intervention to validate AI-generated content, stressing critical thinking and a balanced approach to leverage AI's advantages while mitigating its potential drawbacks.